Analisis Kehilangan Energi Pada Pipa Transmisi SPAM Kecamatan Mempura - Renold Almadya; Siswanto Siswanto; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Clean water obtained by the community District Mempura is still minimal. This is of course caused by many factors such as reservoir and flow in pipes. Water Supply System (WSS) District Mempura using EPANET 2.0 software with 3 (three) alternative transmission pipes each diameter 6 inch, 8 inch and 10 inch. Projection of population of District Mempura using Geometric method until 2035 is 27.262 soul and requirement of clean water equal to 37 liter / second. From 3 (alternative), 10 inch pipe transmission line is used with flow rate 0,79 m / s, head at node A1 equal to 16,13 meter, pressure value 4,25 meter and headloss 2,31 / 1000 meter.Keywords: Head loss, transmission pipes, SPAM, clean water